Protein Kinase MpYAK1 Is Involved in Meristematic Cell Proliferation, Reproductive Phase Change and Nutrient Signaling in the Liverwort Marchantia polymorpha. (8th June 2022) - Shinkawa, Haruka; Kajikawa, Masataka; Furuya, Tomoyuki; Nishihama, Ryuichi; Tsukaya, Hirokazu; Kohchi, Takayuki; Fukuzawa, Hideya
Abstract: Plant growth and development are regulated by environmental factors, including nutrient availability and light conditions, via endogenous genetic signaling pathways. Phosphorylation-dependent protein modification plays a major role in the regulation of cell proliferation in stress conditions, and several protein kinases have been shown to function in response to nutritional status, including dual-specificity tyrosine phosphorylation-regulated kinases (DYRKs). Although DYRKs are widely conserved in eukaryotes, the physiological functions of DYRKs in land plants are still to be elucidated. In the liverwort Marchantia polymorpha, a model bryophyte, four putative genes encoding DYRK homologous proteins, each of which belongs to the subfamily yet another kinase 1 (Yak1), plant-specific DYRK, DYRK2, or pre-mRNA processing protein 4 kinase, were identified. Mp YAK1 -defective male and female mutant lines generated by the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated nuclease 9 (Cas9) system showed smaller sizes of thalli than did the wild-type plants and repressed cell divisions in the apical notch regions. The Mp yak1 mutants developed rhizoids from gemmae in the gemma cup before release. The Mp yak1 lines developed sexual organs even in non-inductive short-day photoperiod conditions supplemented with far-red light. In nitrogen (N)-deficient conditions, rhizoid elongation was inhibited in the Mp yak1 mutants. In conditions of aeration with 0.08% CO2 (v/v) and N depletion, Mp yak1 mutants accumulated higher levels of sucrose and lower levels of starch compared to the wild type. Transcriptomic analyses revealed that the expression of peroxidase genes was differentially affected by MpYAK1. These results suggest that MpYAK1 is involved in the maintenance of plant growth and developmental responses to light conditions and nutrient signaling.